An overview of amines as nutritional supplements to counteract cancer cachexia. Issue 2 (28th March 2014) - de Campos‐Ferraz, Patrícia Lopes; Andrade, Isabel; das Neves, Willian; Hangai, Isabela; Alves, Christiano Robles Rodrigues; Lancha Jr, Antonio Herbert
Abstract : Cancer cachexia is a complex multifactorial syndrome characterized by loss of skeletal muscle mass (with or without loss of fat mass) that cannot be fully reversed by conventional nutritional support and leads to progressive functional impairment. Recently, some amino acids and other amine dietary supplements have been highlighted in medical field due to positive effects upon diseases evolving skeletal muscle atrophy. Therefore, the aim of this brief review is to discuss the putative application of amines as dietary supplements to counteract skeletal muscle wasting on cancer cachexia. Specifically, we focus in two nutritional supplements: (1) branched‐chain amino acids (BCAAs) and (2) creatine. Both BCAAs and creatine may attenuate proteolysis and enhance proteins synthesis in skeletal muscle. Although more experimental studies and clinical trials are still necessary to elucidate this therapeutic application, several evidences have demonstrated that amines supplementation is a promising coadjuvant treatment to cancer cachexia.